Dental anatomy and morphology - Riquieri, Hilton (Batavia : Quintessence Publishing Co, Inc., 2019)
This beautiful atlas conveys not only the practical knowledge of dental anatomy but also the art of sculpting it in wax. The ideal anatomy of each dental structure is described in detail and the waxing techniques are beautifully illustrated step by step for visual reference.
Dental anatomy and morphology -- Contents -- Forewords -- Dedication -- Preface -- Acknowledgments -- Contributors -- SECTION I: Posterior Teeth -- Chapter 1. The Esthetic and Functional Parameters of Posterior Teeth -- Chapter 2. Maxillary First Premolar -- Chapter 3. Maxillary Second Premolar -- Chapter 4. Maxillary First Molar -- Chapter 5. Maxillary Second Molar -- Chapter 6. Maxillary Posterior Quadrant -- Chapter 7. Mandibular First Premolar -- Chapter 8. Mandibular Second Premolar -- Chapter 9. Mandibular First Molar -- Chapter 10. Mandibular Second Molar -- Chapter 11. Mandibular Posterior Quadrant -- SECTION II: Anterior Teeth -- Chapter 12. The Esthetic and Functional Parameters of Anterior Teeth -- Chapter 13. Maxillary Central Incisor -- Chapter 14. Maxillary Lateral Incisor -- Chapter 15. Maxillary Canine -- Chapter 16. Progressive Technique for Maxillary Anterior Teeth -- Chapter 17. Anterior Segment and Full Arch Wax-ups -- Recommended Reading.
Includes bibliographical references and index.
Keywords: Tooth -- anatomy & histology; Dental Models